BREAD PRODUCED FROM COMPOSITE FLOURS USING Saccharomyces cerevisiae ISOLATED FROM LOCAL FERMENTED BEVERAGE (BURKUTU) - Ayoade, Rukayat Biodun; MOHAMMED, S.S.D; AUTA, RICHARD Z (FUDMA Journal of Sciences, 2020)
Composite flour/bread technology is an important area to be properly harnessed in food industries to help reduce the cost of wheat importation in Nigeria. In this study, bread produced from composite flours using Saccharomyces cerevisiae isolated from local fermented beverage (Burkutu) was investigated. Sugar fermentation, carbohydrate utilization and ethanol tolerance tests were carried out in identifying and characterizing the yeast isolates. Composite breads were produced from Wheat Flour (WF) (100%) and its blends with Rice Flour (RF) (40%), Plantain Flour (PF) (40%) and Cassava Flour (CF) (40%) using the straight dough method. The yeast survived in 25% glucose and 15% ethanol, suggesting its usefulness in industrial application. Loaf weights and loaf volumes of the composite bread samples ranged from 318.4 - 355.7 g, and 420.6 - 457.3 mL respectively, with 100% Wheat Bread ranking highest while Composite rice bread the least, using a significant difference of P0.05) in the bread samples analysed. Shelf life assessment of the bread samples at room temperature (26Â±1oC) within the first three days revealed no microbial growth/cell count. Bread produced from the incorporation of cassava with wheat flour was found to be acceptable, with insignificant variation when compared to bread made with 100% wheat flour.
Keywords: Burkutu; Saccharomyces cerevisiae; Yeast isolate; Composite flour; Bread samples